Temporary Work : The Gendered Rise of a Precarious Employment Relationship - Vosko, Leah F. (Book collections on Project MUSE., 2000)
"The first in-depth analysis of temporary work in Canada, this book by Leah F. Vosko examines a number of trends, including the commodification of labour power; the decline of the full-time, full-year job as a norm; and the gendered character of prevailing employment relationships. Spanning the period from the late nineteenth to the late twentieth century, Temporary Work traces the evolution of the temporary employment relationship in Canada and places it in an international context. It explores how, and to what extent, temporary work is becoming the norm for a diverse group of workers in the labour market, taking gender as the central lens of analysis." "Recent scholarship emphasizes that the nature of work is changing, citing the spread of non-standard forms of employment and the rise in women's participation in the labour force. Vosko confirms that important changes are indeed taking place in the labour market, but argues that these changes are best understood in historical, economic, and political context. This book will be invaluable to academics in a variety of disciplines as well as to policy analysts and practitioners in government, industry, and organized labour."--Jacket.